Pengaruh Kepribadian Extraversi terhadap Dimensi Self-Efficacy Karyawan Industri Telekomunikasi Provider Kota Metro - Fahri Adil Bahtera; Ribhan Ribhan (Jurnal Manajemen Bisnis Era Digital, 2025)
This research aims to investigate the impact of extroverted personality traits on the dimensions of self-efficacy among employees in the telecommunications industry in Metro City. The study is grounded in the significance of innovation and employee performance in navigating today’s complex business environment. Employing a quantitative approach with a survey method, the study involved 110 respondents from the telecommunications sector. Data were gathered through questionnaires and analyzed using simple regression analysis. The findings indicate that extroversion has a positive and significant effect on all aspects of self-efficacy: level, generality, and strength. The mean score for extroversion was 4.15, while the mean scores for the self-efficacy dimensions were 4.18 (level), 4.30 (generality), and 4.32 (strength). Regression analysis revealed that extroversion influences the level dimension by 52.9%, generality by 64.8%, and strength by 69.1%. All hypotheses were supported with significance values below 0.05, indicating statistically significant relationships between the variables.